Development and control method for a six-wheeled robot with a Bogie structure - Sylvester, Derry Dexler; Idris, Aiman; Mohamad, Noor Dian Eka Wahyu; Lokman, Nurhafiza; Sufian, Nur Nabila Syafiqah; Kamarulzaman, Mohd Kamal; Hisham, Sakinah; Halim, Qayyum (Academica Press Solutions, 2025)
This study focuses on the development and optimization of a six-wheeled Rocker-Bogie Robot designed for efficient stair navigation in diverse environments. The robot’s design incorporates critical parameters, including wheel placement, motor torque distribution, and suspension geometry, to enhance stability and adaptability. A systematic iterative process improved the robot’s ability to overcome obstacles such as stairs with dimensions of 6 × 30 cm and 8 × 34 cm. The methodology integrates kinematic constraints, contact angle analysis, and motor control optimization to refine performance. Experimental results validated the robot’s capability to ascend and descend stairs while maintaining stability, demonstrating its potential for real-world applications in delivery, healthcare, and maintenance. This work contributes to advancing cost-effective and reliable stair-climbing robotics, paving the way for further enhancements in service robotics for complex indoor and outdoor terrains.